Investigating the Influence of Different L2 Proficiency Measures on Research Results - Zhang, Haiwei; Jiang,Yuhao; Jing Yang (SAGE open, 2020)
Researchers have used different measures to examine participants’ second-language (L2) proficiency, yet it remains unclear how these different measures influence research results on the effect of L2 proficiency on the target variable. The present research explored the modulation effect of four different measures of L2 Chinese proficiency on Chinese phonological awareness (PA). Eighty-four L2 learners of Chinese who spoke English or Arabic as their first language completed four different measures of Chinese proficiency: a self-report measure of years of instruction in Chinese, a simplified Hanyu Shuiping Kaoshi (HSK; a standardized Chinese language proficiency test), a reading comprehension test, and a Chinese character recognition test. The overall results of t tests and multiple regression analysis revealed that different measures of L2 proficiency led to various findings on the effect of L2 proficiency on Chinese PA. Compared with the other three measures, the HSK, a comprehensive examination of L2 Chinese proficiency, yielded the most consistent and reliable results with the largest effect size. Our findings contribute to the current understanding of L2 proficiency measures and to future efforts for the improvement of L2 proficiency tests for research purposes.
Keywords: Chinese; Chinese proficiency test; College Students; different L2 proficiency measures; Evaluation Methods; Foreign Countries; HSK test; Interdisciplinary; Language Proficiency; Language Tests; Phonological Awareness; Second Language Learning; Social Sciences; Social Sciences - Other Topics; Test Content